Resource Conservation of Food Crops, Medicinal Plant and Dyes in Karang Bajo, North Lombok District - Jupri, Ahmad; Isrowati, Isrowati; Hidayati, Lilik; Adelia, Adelia; Sintia, Nuraema; Ningsih, Niati; Hidayah, Nurul; Royani, Andhini Dwi Mifta; Wahyudi, Alpan; Wijdan, Ifad (Jurnal Biologi Tropis, 2025)
Karang Bajo Village, located at the foot of Mount Rinjani, has a wealth of cultural and environmental heritage that supports the sustainability of agriculture and the potential of local plants. This study aims to identify and inventory food plants, medicines and natural dyes in Karang Bajo Village, North Lombok Regency. The research method was by conducting in-depth interviews with the determination of informants by random sampling, observation and documentation. The results of the study showed that many types of plants have the potential as sources of food, traditional medicine and natural dyes. Types of food plants that are often consumed by the community are taro, sweet potatoes, cassava and soybeans. Types of medicinal plants used by the community are ginger, galangal, aloe vera and mengkudu. Natural dye plants that are still used are turmeric, dragon fruit, butterfly pea flowers and pandan leaves. Efforts to conserve local plants carried out by the local community show an awareness of the importance of maintaining the local environment and culture. The use and preservation of local plants aims to maintain the sustainability of natural resources and the environment.